Methysergide attenuates systemic burn edema in rats - Hernekamp, Jochen-Frederick; Hu, Sissi Xi; Schmidt, Karsten; Walther, A.; Lehnhardt, Marcus; Kremer, Thomas (Microvascular research, 2013)
Background - Thermal injuries of more than 20% total body surface area result in systemic shock with generalized edema. Burn shock is induced by a variety of mediators, mainly immunomodulative cytokines. Administration of methysergide (Met), a serotoninergic receptor blocking agent, reduces generalized edema in endotoxemia in rats. In this study we evaluated the systemic effects of Met after thermal injury. - Methods - Donor rats (DR [n=8]) for positive controls and study groups underwent thermal injury (100°C water, 30% TBSA (Total Burn Surface Area), 12s). Shamburn plasma was harvested after a shamburn procedure ([n=4], 37°C water, 30% TBSA, 12s). Plasma was harvested 4h posttrauma and was transferred to healthy individuals. Recipient animals were randomized in 3 groups (1: burnplasma, 2: shamburn, 3: burnplasma plus methysergide (Bolus of 1mg/kg body weight)). Intravital microscopy was performed in mesenteric venules (0/60/120min). Edema was assessed by FITC-albumin extravasation. Leukocyte sticking (cells/mm2) and microhemodynamic parameters were assessed. - Results - Significant systemic capillary leakage was observed after burnplasma-transfer. Edema formation was significantly lower in negative controls. Application of methysergide reduced FITC-efflux to baseline levels. Adherent leukocytes increased in all groups, at 120min the amount of adherent leukocytes in positive controls was significantly higher in comparison to shamburn, differences to MET-groups were not significant. - Conclusion - Burnplasma transfer to healthy individuals induces leukocyte activation and plasma extravasation and this effect is reduced by administration of Met. This may be attributed to leukocyte dependent as well as independent mechanisms. Evaluation of more specific serotoninergic antagonists is required to distinguish between systemic and local effects.